2017
DOI: 10.1155/2017/5806185
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Response Relationship between PM2.5and Daily Respiratory Deaths in China: A Systematic Review and Metaregression Analysis of Time-Series Studies

Abstract: The association between the particulate matters with aerodynamic diameter ≤ 2.5 μm (PM2.5) and daily respiratory deaths, particularly the concentration-response pattern, has not been fully examined and established in China. We conducted a systematic review of time-series studies to compile information on the associations between PM2.5 concentration and respiratory deaths and used metaregression to assess the concentration-response relationship. Out of 1,957 studies screened, eleven articles in English and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…According to recent clinical studies, both long and short period exposure to PM2.5 could increase the prevalence and mortality of respiratory diseases [2][3][4]. In our clinical application, we discovered that MGMD and YPFP could relieve the respiratory symptoms caused by hazy weather.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to recent clinical studies, both long and short period exposure to PM2.5 could increase the prevalence and mortality of respiratory diseases [2][3][4]. In our clinical application, we discovered that MGMD and YPFP could relieve the respiratory symptoms caused by hazy weather.…”
Section: Discussionmentioning
confidence: 78%
“…The average annual concentration of PM2.5 in Chinese urban area in 2016 (51 µg/m 3 ) was far beyond the level WHO recommended (12 µg/m³). Recent epidemiological studies have shown that both long and short term exposure to PM2.5 are closely associated with respiratory diseases which increased the risk of chronic obstructive pulmonary disease (COPD), lung cancer, asthma and pneumonia [2][3][4]. The mechanisms of PM2.5-induced respiratory system injury have been investigated including in ammatory response, oxidative stress, genotoxicity, and imbalanced intracellular calcium homeostasis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies conducted mainly in developing countries have associated PM 2.5 with all cause and cause-specific mortality [2,3,4,5,6,7]. These studies have evaluated short-term and long-term PM 2.5 exposure on mortality, primarily cardiovascular and respiratory deaths [3,4,8], but also some kinds of cancer [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Even in high-income countries, the percentage is as high as 56% [1]. Air pollution has a substantial impact on human health and has become a global public health risk [2].…”
Section: Introductionmentioning
confidence: 99%